The Students’ Perception of the Teaching Methods and Media on Mandarin Conversation Online Learning at University - Diana, Lani; Sutandi, Septerianie (Universitas Dian Nuswantoro, 2022)
Mandarin is the second most widely used foreign language in the world. Teaching Mandarin needs appropriate teaching methods and media to achieve learning objectives. Researchers researched the learning of Mandarin conversation in one of the private universities of Bandung to analyze the influence of teaching methods applied and teaching media used during online learning. The research involved a descriptive analysis method with a qualitative approach. Data collection was done by filling out questionnaires and interviews to determine the alignment of teaching methods and teaching media used and the influence of teaching methods and media on online learning of Mandarin conversation in that university. The results showed that learning Mandarin conversation online using three learning methods (audio-lingual, communicative approach, and task-based methods) and online teaching media Zoom Meeting, YouTube, Morning, and WhatsApp was perceived as effective. It could improve university students’ Mandarin conversation skills.